The Implementation of Direct Local Election (Pilkada) and Money Politics Tendencies: The Current Indonesian Case - Noor, Firman; Siregar, Sarah Nuraini; Hanafi, Ridho Imawan; Sepriwasa, David (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Circulating debates concerning the intense influence of direct local election towards money politics remains ongoing among Indonesian scholars. This article demonstrates several aspects indicating the relationship between direct local election (Pilkada) and money politics. In more specific rhetoric, current practices in money politics tend to occur before and during the election day, engaging political actors, voters, and soaring capital. As the novelty of this article, the findings reveal that the likelihood of money politics would most occur within the environment where the existing regulation encourages corruption. Hence, people have less concern to support a fair election, inevitably due to the weak law enforcement, exacerbated by disengagement of political parties.